2021
DOI: 10.3390/biomedicines9101335
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Age-Related Diseases

Abstract: Telomeres are at the non-coding ends of linear chromosomes. Through a complex 3-dimensional structure, they protect the coding DNA and ensure appropriate separation of chromosomes. Aging is characterized by a progressive shortening of telomeres, which compromises their structure and function. Because of their protective function for genomic DNA, telomeres appear to play an important role in the development and progression of many age-related diseases, such as cardiovascular disease (CVD), malignancies, dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 201 publications
(214 reference statements)
0
64
0
Order By: Relevance
“…In general, being physical active, not smoking and having good sleep quality are associated with a reduced risk of morbimortality for the main chronic diseases [ 8 , 9 , 10 , 11 , 144 , 145 , 146 , 147 ]. There is a challenge in searching for the best biomarker of aging and despite these limitations and the advantage of measuring a combination of biomarkers instead of only one [ 148 , 149 ], TL is the most extensively studied biomarker of age-related diseases [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In this regard, many results have been obtained focusing on the association between TL, aging, cardiovascular diseases, diabetes, obesity and mortality [ 35 , 36 , 37 , 38 , 39 , 40 , 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, being physical active, not smoking and having good sleep quality are associated with a reduced risk of morbimortality for the main chronic diseases [ 8 , 9 , 10 , 11 , 144 , 145 , 146 , 147 ]. There is a challenge in searching for the best biomarker of aging and despite these limitations and the advantage of measuring a combination of biomarkers instead of only one [ 148 , 149 ], TL is the most extensively studied biomarker of age-related diseases [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In this regard, many results have been obtained focusing on the association between TL, aging, cardiovascular diseases, diabetes, obesity and mortality [ 35 , 36 , 37 , 38 , 39 , 40 , 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a challenge in searching for the best biomarker of aging and despite these limitations and the advantage of measuring a combination of biomarkers instead of only one [ 148 , 149 ], TL is the most extensively studied biomarker of age-related diseases [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In this regard, many results have been obtained focusing on the association between TL, aging, cardiovascular diseases, diabetes, obesity and mortality [ 35 , 36 , 37 , 38 , 39 , 40 , 148 , 149 ]. Therefore, the demonstration of an effect of these lifestyle factors on TL could provide important information on the mechanisms by which these factors have protective health effects, as well as providing evidence to validate TL as a good biomarker of aging with a good capacity to capture healthy lifestyle interventions based on these factors.…”
Section: Discussionmentioning
confidence: 99%
“…The silencing of TERF1 can lead to genomic instability, chromosome end fusion, and failure in regulating telomerase recruitment and telomere maintenance. It is relevant to point out, that some studies reported an association between short telomeres and early death ( Jaskelioff et al, 2011 ; Mather et al, 2011 ; Gruber et al, 2021 ). Furthermore, shortened telomeres or telomerase mutations were observed in people with diseases characterized by premature aging ( Fani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progressive impairment of genomic integrity and genomic instability are key drivers of the aging process [8,9]. With every cell division, telomeres shorten a little bit due to incomplete replication of the DNA lagging strand.…”
Section: Introductionmentioning
confidence: 99%
“…The unique role of telomeres in the aging process has led to the idea that TL could be a useful surrogate marker of biological age. In fact, human and animal studies have shown that in age-related diseases, such as atherosclerosis, diabetes and rheumatic diseases, TL is reduced in the affected tissues [8,[12][13][14][15]. As the analysis of TL in solid tissues requires an invasive biopsy, TL in peripheral blood leucocytes (LTL) has been proposed as surrogate marker for TL in other tissues.…”
Section: Introductionmentioning
confidence: 99%